2020
DOI: 10.1038/s41598-020-78456-2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous imaging of hard and soft biological tissues in a low-field dental MRI scanner

Abstract: Magnetic Resonance Imaging (MRI) of hard biological tissues is challenging due to the fleeting lifetime and low strength of their response to resonant stimuli, especially at low magnetic fields. Consequently, the impact of MRI on some medical applications, such as dentistry, continues to be limited. Here, we present three-dimensional reconstructions of ex-vivo human teeth, as well as a rabbit head and part of a cow femur, all obtained at a field strength of 260 mT. These images are the first featuring soft and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 37 publications
(45 reference statements)
1
46
0
Order By: Relevance
“…As an alternative to radiography, other imaging technologies without ionizing radiation (e.g., ultrasonography or MRI) are being actively studied. It was recently found that a method using MRI can be used for both soft tissue and hard tissue observation, and based on this, it started to gain considerable interest from the periodontal disease research community [137,160]. Lastly, with the integration of state-of-the-art image processing algorithms and artificial intelligence technology, higher accuracy in diagnosis and better prediction in prognosis are expected [98,99,[161][162][163].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to radiography, other imaging technologies without ionizing radiation (e.g., ultrasonography or MRI) are being actively studied. It was recently found that a method using MRI can be used for both soft tissue and hard tissue observation, and based on this, it started to gain considerable interest from the periodontal disease research community [137,160]. Lastly, with the integration of state-of-the-art image processing algorithms and artificial intelligence technology, higher accuracy in diagnosis and better prediction in prognosis are expected [98,99,[161][162][163].…”
Section: Future Directionsmentioning
confidence: 99%
“…However, a recent study suggested overcoming the limitation of hard tissue imaging using MRI and demonstrating that using MRI can be effective for both soft tissue and hard tissue observation. Algarin et al designed a special-purpose MRI scanner (DentMRI-Gen I) capable of producing high-quality combined images of soft and hard biological tissues at sub-Tesla fields (260 mT) [ 137 ]. However, simultaneous imaging of soft and hard tissues using MRI requires more clinical validation, so there are remains opportunities for technology development.…”
Section: Diagnosis With the Imaging Toolsmentioning
confidence: 99%
“…The main constraints we considered for the design of the prepolarizer were: i) it must be a module that can be easily installed into and removed from the "DentMRI -Gen I" system [17]; ii) it must produce a prepolarization field significantly higher than the evolution field 𝐵 0 ≈ 0.26 T; and iii) it must be possible to ramp the field up and down in less than 10 ms to enable PMRI of hard biological tissues.…”
Section: P a Magnetic Mechanical And Thermal Designmentioning
confidence: 99%
“…III-B). The control system is based on a RadioProcessor-G console from SpinCore Technologies Inc. and is described elsewhere [17]. To control the prepolarizer via the console, we use a TTL line which triggers the IPM-16P switches after optical decoupling in the FT1 module (Eagle Harbor Technologies Inc.).…”
Section: B Electronics Designmentioning
confidence: 99%
See 1 more Smart Citation